Factors Impacting Students' Learning Behavioral Intentions with Online Teaching in Design Education: A Case Study of a Public University in Nanchang, China - Xin, Jin (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examines factors influencing students’ learning behavior intentions in online design education. It aims to enhance understanding of how online learning environments can be optimized to meet evolving educational needs. Research design, data and methodology: The study develops hypotheses and constructs a model based on current research and relevant theories. Data is obtained through a questionnaire survey, which is then statistically analyzed to test the proposed theoretical hypotheses. The methodology includes evaluations such as Item-Objective Congruence (IOC), Pilot Testing, and Multiple Linear Regression (MLR) analysis to assess the reliability and validity of the findings, focusing on perspectives from both teachers and students. Results: The study identifies key factors influencing students’ learning intentions in online design education, emphasizing the importance of communication, engagement, and the learning environment. Additionally, challenges such as the lack of face-to-face interaction and emotional connectivity are highlighted as significant barriers to effective learning. Conclusions: This study offers theoretical and empirical insights to improve online design education. Educators can apply these findings by fostering interactive learning spaces, incorporating real-time feedback, and using collaborative projects to enhance engagement. Recognizing these critical factors allows educators to refine their teaching strategies, foster motivation, and improve learning outcomes in online design education.